2010
DOI: 10.1007/s11916-010-0093-y
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Morphine on Glial Cells as a Potential Therapeutic Target for Pharmacological Development of Analgesic Drugs

Abstract: Opioids have played a critical role in achieving pain relief in both modern and ancient medicine. Yet, their clinical use can be limited secondary to unwanted side effects such as tolerance, dependence, reward, and behavioral changes. Identification of glial-mediated mechanisms inducing opioid side effects include cytokine receptors, kappa-opioid receptors, N-methyl-D-aspartate receptors, and the recently elucidated Toll-like receptors. Newer agents targeting these receptors such as AV411, MK-801, AV333, and S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 58 publications
0
26
0
Order By: Relevance
“…Previous studies have shown that opioid receptors are [3,32,33] . After chronic or acute exposure to morphine, activated neurons and glia exhibit increased expression of pro-infl ammatory cytokines, such as TNF-α, IL-1β, IL-6 [19,34,35] , and chemokines [36,37] .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that opioid receptors are [3,32,33] . After chronic or acute exposure to morphine, activated neurons and glia exhibit increased expression of pro-infl ammatory cytokines, such as TNF-α, IL-1β, IL-6 [19,34,35] , and chemokines [36,37] .…”
Section: Discussionmentioning
confidence: 99%
“…Maybe not -it may be able to block the gap junctions of inhibitory interneuron by itself. Glial cells can be inhibited by opioids, because they have opioid receptors (31), and glial cells are also connected by gap junctions (23), so it is probable that a proportion of morphine analgesia arises through inhibition of interconnected glial cells and reduction of the release of their inflammatory mediators (31); in such circumstances carbenoxolone would inhibit the glial cell gap junctions; in other words, carbenoxolone inhibits glial cell inhibition produced by morphine, thus alleviating morphine analgesia. By itself, carbenoxolone can inhibit glial cell gap junctions, but in this state, carbenoxolone inhibits glial cell activity, reducing the release of inflammatory mediators by glial cells and producing analgesia; these hypotheses also require further investigation.…”
Section: Gap Junctions' Role In Morphine Analgesiamentioning
confidence: 99%
“…However, opioids are reported to have suboptimal therapeutic efficacy against neuropathic pain (Bleeker et al, 2001;Cherny et al, 1994). There have been reports that chronic morphine treatment leading to 'morphine tolerance' may indeed induce the death of neurons (Hameed et al, 2010;Mao et al, 2002). The ineffectiveness of morphine in the context of neuropathic pain may be due to the reduced number of presynaptic opioid receptors due to the degeneration of primary afferent neurons, which is in turn caused by nerve damage.…”
Section: Opioid Tolerance In Neuropathic Painmentioning
confidence: 99%